Community Empowerment for Older Persons - Siswanto, Hadi (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: The number of older persons continues to increase, both in developed and developing countries; and it will cause problems if lacks attention. They are often perceived as a burden to their families, the community, and even as a burden to the country. The government is very concerned towards the older persons based on legal and law to improve the prosperity of older persons. Many activities have also been conducted, but not all have been considered as a full integrated tool in solving problems dealing with the older person, especially elderly, such as POSYANDU (Intergrated Service Unit), POSDAYA (Family Empowering Unit), and POSBINDU (Individual Development Unit). Indonesia has a philosophical basis (norms, social, and cultural aspects) that able to be used for the mobilization of communities to deal with the older persons, either through the government sector, private and individual sectors, as well as communities. Steps that can be used with the method of research and development, and also organizing society based on social values and local culture. However, it is realy fact the Indonesian people still do not know about the issues of the elderly. Accordingly, advocacy and dissemination of information, including the approach to normative re-educative as life-cycle, should be done through a variety of its developmentally appropriate media and, especially also, in line with the development of science and technology that enabling and reinforcing the solutions should be done. Empowerment of the elderly community should be driven and as basis evidence for developing the noble values of nation, build friendship, and communication as a container services so that formed the healthy and developed families.KEY WORD: Demography; Older Persons; Degenerative; Long Life Cycle; Community Empowerment.Â RESUME: âPemberdayaan Masyarakat Lanjut Usiaâ. Penduduk lanjut usia terus meningkat, baik di negara-negara maju maupun berkembang; dan ianya akan menyebabkan masalah kalau kurang perhatian. Orang-orang lansia (lanjut usia) sering dipersepsikan sebagai beban keluarga, beban masyarakat, dan bahkan beban negara. Pemerintah sangat peduli terhadap orang-orang lansia berdasarkan hukum dan perundangan-undangan untuk meningkatkan kesejahteraan mereka. Banyak kegiatan juga telah dilakukan, tetapi tidak semua dipertimbangkan sebagai wahana yang terintegrasi penuh dalam memecahkan masalah yang berhubungan dengan orang-orang tua, terutama para lansia, seperti POSYANDU (Pos Pelayanan Terpadu), POSDAYA (Pos Pemberdayaan Keluarga), dan POSBINDU (Pos Pembinaan Individu). Indonesia memiliki dasar filosofis (norma, sosial, dan aspek budaya) yang dapat digunakan untuk mobilisasi masyarakat yang berkenaan dengan orang-orang lansia, baik melalui sektor pemerintah, sektor swasta dan individu, maupun masyarakat. Langkah-langkah yang digunakan bisa dengan metode riset dan pengembangan, dan juga pengorganisasian masyarakat yang didasari oleh nilai-nilai sosial dan budaya setempat. Walaupun demikian, ternyata masyarakat Indonesia masih belum banyak tahu tentang isu-isu orang lansia. Karena itu, advokasi dan penyebaran informasi, termasuk pendekatan normatif re-edukatif sebagai siklus hidup, harus dilakukan melalui berbagai media sesuai dengan tahapan perkembangannya dan, terutama juga, sejalan dengan perkembangan ilmu pengetahuan dan teknologi yang memungkinkan untuk memperkuat solusi tersebut harus dilakukan. Pemberdayaan masyarakat lansia harus didorong dan sebagai bukti dasar untuk mengembangkan nilai-nilai luhur bangsa, membangun persahabatan, dan komunikasi sebagai wahana melalui layanan agar terbentuk keluarga yang sehat dan berkembang. KATA KUNCI: Demografik; Orang-orang Lansia (Lanjut Usia); Degeneratif; Pembinaan Sepanjang Hayat; Pemberdayaan Masyarakat.About the Author: Dr. Hadi Siswanto is a Senior Lecturer and Dean of the Faculty of Health Sciences URINDO (University of Respati Indonesia), Jalan Bambu Apus I No.3 Cipayung, Jakarta Timur, Indonesia. For academic interests, the author can be contacted via his mobile phone at: +628129865869 or e-mail at: hadisis_viva@yahoo.comHow to cite this article? Siswanto, Hadi. (2016). âCommunity Empowerment for Older Personsâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.9(1) May, pp.143-152. Bandung, Indonesia: Minda Masagi Press and UPI Bandung, ISSN 1979-0112. Chronicle of the article: Accepted (December 1, 2015); Revised (March 24, 2016); and Published (May 20, 2016).